Inspired Preparation of Zinc Oxide Nanocatalyst and the Photocatalytic Activity in the Treatment of Methyl Orange Dye and Paraquat Herbicide - Ghaida H. Munshi; Amal M. Ibrahim; Laila M. Al-Harbi (International Journal of Photoenergy)
As the need to use green chemistry routes increases, environmentally friendly catalytic processes are a demand. One of the most important and abundant naturally occurring catalysts is chlorophyll. Chlorophyll is the first recognized catalyst; it is a reducing agent due to its electron-rich structure. The effects of spinach on the preparation of zinc oxide nanoparticles and the photocatalytic degradation of methyl orange and paraquat in sunlight and under a UV lamp and photocatalytic degradation in sunlight were studied. Different parameters of the catalytic preparation process and photocatalytic degradation process were studied. Characterization of differently prepared samples was carried out using different analytical techniques such as XRD, SEM, and EDX and finally the photocatalytic activity towards decomposition of methyl orange and paraquat.